Design And Build A Mikrotik Network Learning Media Using The Waterfall Method And Randomizing Questions Using The Fisher-Yates Shuffle Method - Josi Maduri; Achmad Fauzi; Mill alfisyahri (International Journal of Health Engineering and Technology, 2022)
The development of the world of information today is increasingly entering various fields that are trying to take advantage of today's information technology. The problem of developing the quality of education and helping school facilities to produce smart children and assisting teachers in teaching, as well as making teachers creative and helping children learn smart, this technology is also very helpful for children to actively study at home so they can save costs and tools used , and this learning application can divert the habits of children who previously only played cellphones but now can play cellphones while studying so that students don't get bored.